Quantification and nitrogen fixation of cyanobacteria in rice field soils of Bangladesh (Bangladesh Journal of Botany, 2008)
Quantification of cyanobacterial population and nitrogen fixation of 18 heterocystous cyanobacteria isolated from rice fields soils of 11 districts of Bangladesh have been studied. The taxa recorded were, namely Nostoc linckia, N. carneum, N. ellipsosporum, N. piscinale, Anabaena oryzae, Scytonema mirabile, Calothrix marchica and Hapalosiphon welwetschii. The number of cyanobacterial population varied significantly ranging from 14.6 × 104 to 141.0 × 104/g soil. N2-fixation of Nostoc linckia isolated from rice fields of Dhaka and Brahmanbaria ranged from 1.84 to 8.13 mg N 50/ml. However, the potentiality of other species was more or less similar. Single correlation study suggests that quantitative variation in cyanobacterial population was significantly related positively to soil reaction, available P and available S and negatively to total N content of soil. However, multiple correlations reflects that variation of cyanobacterial population was due to cumulative contribution of all the variables.  Key words: Cyanobacteria, Quantification, N2-fixation, Rice field soil doi:10.3329/bjb.v37i2.1728 Bangladesh J. Bot. 37(2): 183-188, 2008 (December)